Diversity Of Urban Socio-Ecological Supports Among Multi-Ethnic Youth In Urban Areas - Ariffuddin Kamari, Mohd; Razaq Ahmad, Abdul; Yahya Mohamed Ariffin, Mohd; Abd. Rahman, Norshariani; Zulanidi, Hutkemri; Lionardo, Andries (International Journal of Psychosocial Rehabilitation, 2020)
Youth life depends on diversity of urban socio-ecological support in their environment to achieve a healthy life. Thus, the study aims to determine the level of diversity of urban social ecological support among multiethnic youth in urban areas. This study used stratified random sampling involving 2400 multi-ethnic youths living in six Kuala Lumpur City zones. Data were obtained using questionnaire as research instrument. A pilot study that was conducted on 203 youths showed that all items had high reliability with a Cronbach Alpha value of 0.8 and were suitable to be used in the actual study. The study data were analyzed using descriptive analysis involving mean, standard deviation and percentages. The findings show that the overall level of social support for youth survival in Kuala Lumpur are at a high level (mean 3.821). In term of the majority, 65.4% of the respondents indicated that social ecology support was high, while 33.6% stated social support was moderate and only 1.0% indicated low social ecological support level. Among the aspects studied in social support are family support, virtual platform support and local community support while the level of institutional support is moderate. Results from this study may help in giving the input to various parties such as the Local Council, the Ministry of Youth and related NGOs in making plans either physically or socio-economically which will affect the youth development in the city.